2005
DOI: 10.1038/sj.cr.7290274
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 3 expression in C57BL/6J mouse embryo epidermis and the correlation with its differentiation

Abstract: Epidermal-type transglutaminase 3 (TGM3) is involved in the cross-linking of structural proteins to form the cornified envelope in the epidermis. In the present study, we detected the expression of TGM3 in the mouse embryo using RT-PCR. TGM3 mRNA is weakly presented from E11.5 to E14.5 and increases significantly from E15.5 to birth. Then we determined the spatial and temporal expression pattern of TGM3 in the skin and other organs by in situ hybridization. We found a deprivation of TGM3 in skin at E11.5, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…The question was whether the loss of autophagy was the real reason for the enhanced cell death, since Atg5 interacts with Fas-associated death domain (FADD) protein and the anti-apoptotic protein Bcl-x L (Pyo et al, 2005; Yousefi et al, 2006). Atg5 may regulate apoptosis through the extrinsic or intrinsic cell death pathways (Zhang et al, 2005). …”
Section: Autophagy In T Lymphocyte Homeostasis: Different Genetic Modmentioning
confidence: 99%
“…The question was whether the loss of autophagy was the real reason for the enhanced cell death, since Atg5 interacts with Fas-associated death domain (FADD) protein and the anti-apoptotic protein Bcl-x L (Pyo et al, 2005; Yousefi et al, 2006). Atg5 may regulate apoptosis through the extrinsic or intrinsic cell death pathways (Zhang et al, 2005). …”
Section: Autophagy In T Lymphocyte Homeostasis: Different Genetic Modmentioning
confidence: 99%
“…These results together indicated that, although TG2/Gh of RA-pretreated skin could act as transamidase in vitro, in intact skin, it revealed another enzyme activity of its own at a physiological concentration of Ca ++ . Indeed, it is reported that terminal differentiation of keratinocytes accompanying in TG1, 3 or 5 (Steinert et al, 1996;Zhang et al, 2005;Candi et al, 2002) is induced by high concentration of Ca ++ (Reiss and Zhou 1989).…”
Section: In Situ and In Vitro Transamidation Activity Of Tg In Ra-prementioning
confidence: 99%
“…The most characteristic enzyme function of the transglutaminase family is calcium-dependent transamidation activity; the formation of ε-(g-glutamyl)lysine cross-links between proteins, resulting in polymerization. TG1, TG3 and TG5, the transglutaminase family, are found in mammalian keratinocytes and play an important role in the formation of the stratum corneum in the skin by the introduction of cross-links into proteins (Steinert et al, 1996;Zhang et al, 2005;Candi et al, 2002). In addition to transamidation activity, TG2/Gh functions as a signal-transducing GTP-binding protein (Nakaoka et al, 1994) from classical Gcoupled receptors, serine/threonine kinase (Mishra and Murphy 2004), and a protein-disulfide isomerase that regulates adenylate cyclase (Tucholski and Johnson 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Among a total of 32 genes identified (9 + 23; Table 1), 28 genes (the exceptions being Prdm1 , Calml5 (calmodulin-like 5), Foxe1 (forkhead box E1), and Tfap2a (transcription factor AP-2 alpha)) were also found to be expressed in normal differentiated keratinocytes in mouse oral mucosa [53], the gene expression data of which were obtained from GEO, an accession number of GSE28035. In these genes, it has been reported that Evpl (envoplakin) [35], Scel (sciellin) [4], Tgm1 [8], and Tgm3 [56] are involved in the development of epidermis. In this study, of particular interest was our identification of the skin development-associated gene network D, whose core contains Cdkn1a , Egfr , and Fos derived from upregulated genes in cluster Up-II or Up-III.…”
Section: Discussionmentioning
confidence: 99%